Optimising case definitions of upper limb disorder for aetiological research and prevention: a review. Issue 1 (17th October 2011) - Palmer, Keith T; Harris, E Clare; Linaker, Cathy; Cooper, Cyrus; Coggon, David
Abstract : Experts disagree about the optimal classification of upper limb disorders (ULDs). To explore whether differences in associations with occupational risk factors offer a basis for choosing between case definitions in aetiological research and surveillance, we analysed previously published research. Eligible reports (those with estimates of relative risk (RR) for >1 case definition relative to identical exposures were identified from systematic reviews of ULD and occupation and by hand-searching five peer-review journals published between January 1990 and June 2010. We abstracted details by anatomical site of the case and exposure definitions employed and paired estimates of RR, for alternative case definitions with identical occupational exposures. Pairs of case definitions were typically nested, a stricter definition being a subset of a simpler version. Differences in RR between paired definitions were expressed as the ratio of RRs, using that for the simpler definition as the denominator. We found 21 reports, yielding 320 pairs of RRs (82, 75 and 163 respectively at the shoulder, elbow, and distal arm). Ratios of RRs were frequently ≤1 (46%), the median ratio overall and by anatomical site being close to unity. In only 2% of comparisons did ratios reach ≥4. We conclude that complex ULD case definitions (e.g. involving physical signs, more specific symptom patterns, and investigations) yield similar associations with occupational risk factors to those using simpler definitions. Thus, in population-based aetiological research and surveillance, simple case definitions should normally suffice. Data on risk factors can justifiably be pooled in meta-analyses, despite differences in case definition.